Determination of cadmium in commercial tobacco by EMFAAS - Carrone, Guillermo Alejandro (2018)
In this work we present the use of EMFAAS (Electrothermal Metallic Furnace Atomic Absorption Spectroscopy) for the determination of Cd in the tobacco cigarettes of five commercial brands. Optimization of the experimental conditions was done by controlling the sample flow rate and the temperature of both the injection capillary and the atomization cell. The determination was made in the whole cigarettes, filters and ashes of the cigarettes once consumed, cases in which the Cd concentration is much lower and its quantification is more difficult. For the validation of the results, the ICP-OES technique was used, obtaining good agreement within the experimental error. The results show that EMFAAS is a promising tool for the determination of volatile analytes.